Museum Visitors’ Interest on Virtual Tours in COVID-19 Situation - POURMORADIAN, Samereh; FARROKHI, Omid SALEK; HOSSEINI, Seyedeh Yasamin (Journal of Environmental Management and Tourism; Vol 12 No 4 (2021): JEMT Volume XII Issue 4(52) Summer 2021, 2021)
The pandemic of COVID-19 has significantly impacted the tourism industry in worldwide. The main objective of this research was to explore the desire of virtual museums tourists during the quarantine regulation under impact of COVID-19 pandemic. In this light, we considered the four main step of the quarantine lockdown phase in Spain. During these phases the availability of six types of virtual museums were evaluated to figure out the visitors’ interest. The results were obtained by analysing the number and kind of the visits being recorded in the virtual museum’s tours while Spanish inhabitation used to stay at homes for long days, weeks and even months. According to the results, in the zero-quarantine phase, the highest amount of visitors tend to visits the museum parks. While the science museums were received less visits. However, overall results indicated that the reduction of strictures during the quarantine period while the intensity of people's interest were decreased. Based on the results, we conclude that this research makes significant contribution for tourism research and will benefit the decision makers and stakeholders for developing virtual tourism industry further. We also conclude that for new approaches in the post-corona, special attention should be paid to the new interest developed by tourists during the quarantine period.